1990
DOI: 10.1068/a220615
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Distribution of Benefits and Costs in River-Basin Schemes: A Cooperative Game Approach

Abstract: River-basin developments inevitably require participation by numerous entities (for example, riparians and external funding agencies). The division of the costs and benefits consequent to the scheme is further complicated by time schedules for implementation. In this paper the extension of cooperative game theory to temporal allocations is explored. The approach is illustrated with an example problem involving three riparians and two time periods. Propensities to disrupt are incorporated in the cooperative gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…From the viewpoint of AJO, the only unilateral improvement is changing the current state to u 0 1 : fA, À B, C, À Dg by not choosing strategy B. In this situation, the payoff will change to [12,2]. The state of equilibrium must be a desirable scenario after one unilateral move by both stakeholders.…”
Section: Stakeholder Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…From the viewpoint of AJO, the only unilateral improvement is changing the current state to u 0 1 : fA, À B, C, À Dg by not choosing strategy B. In this situation, the payoff will change to [12,2]. The state of equilibrium must be a desirable scenario after one unilateral move by both stakeholders.…”
Section: Stakeholder Strategiesmentioning
confidence: 99%
“…A large number of studies have found the theory useful and applied it to problems of water resources allocation and management. [2][3][4][5][6][7][8] Conflicts in these studies are often handled in cooperative form and a coalition is established among the stakeholders, as investigated by Collins and Frydenlund, 9 to form strategic groups into an agent-based model through cooperative game theory approaches. Due to escalating water shortage and the growing disputes over water withdrawal, it is almost impossible to employ cooperative games to solve water allocation problems and satisfy the stakeholders, especially when the stakeholders have different interests and are not politically on a par with each other.…”
Section: Introductionmentioning
confidence: 99%
“…Every player in the game has to adopt the strategy in the contract. Some research adopted a cooperative game to analyze the interactions between players when the issue involved 'positive externality' (Dufournaud and Harrington, 1990;Kucukmehmetoglu and Guldmann, 2004;Lubell et al, 2010;Tsang and Jim, 2011). The other type of game, noncooperative, emphasizes personal behavior without the restriction of any contract or agreement.…”
Section: Introductionmentioning
confidence: 99%
“…The model is a linear program that computes equilibrium prices for both water and technology. Finally, one should mention the extensions of the traditional core constraints proposed by Dufournaud and Harrington (1990), whereby both the spatial and the temporal patterns of costs and benefits from river development are considered, and coalitions are defined across periods.…”
mentioning
confidence: 99%